TRIM21 is a novel regulator of Par-4 in colon and pancreatic cancer cells. Issue 1 (2nd January 2017) - Nguyen, Jeffrey Q.; Irby, Rosalyn B.
ABSTRACT: The prostate apoptosis response protein 4 (Par-4) is a tumor-suppressor that has been shown to induce cancer-cell selective apoptosis in a variety of cancers. The regulation of Par-4 expression and activity is a relatively understudied area, and identifying novel regulators of Par-4 may serve as novel therapeutic targets. To identify novel regulators of Par-4, a co-immunoprecipitation was performed in colon cancer cells, and co-precipitated proteins were identified by mass-spectometry. TRIM21 was identified as a novel interacting partner of Par-4, and further shown to interact with Par-4 endogenously and through its PRY-SPRY domain. Additional studies show that TRIM21 downregulates Par-4 levels in response to cisplatin, and that TRIM21 can increase the resistance of colon cancer cells to cisplatin. Furthermore, forced Par-4 expression can sensitize pancreatic cancer cells to cisplatin. Finally, we demonstrate that TRIM21 expression predicts survival in pancreatic cancer patients. Our work highlights a novel mechanism of Par-4 regulation, and identifies a novel prognostic marker and potential therapeutic target for pancreatic cancer.